КИШИ ЖАСТАҒЫ БАЛАЛАРДЫ САНАЎҒА ҮЙРЕТИЎ МАШҚАЛАЛАРЫ - Пахратдинова, Т. (FAN va JAMIYAT, 2020)
The article is devoted to the study of children's games of the Karakalpaks that have reached to this day and serve to educate and accumulate the experience and skills necessary in everyday life. The value of games is that they contribute to the education and development of students. The game is one of the means of forming psychological formations - thinking, attention, memory. The article emphasizes the importance of national games as a factor that helps to the development of abilities, enriches knowledge, broadens the horizon and promotes children's activities.